Impact of human resource management towards organisational performance: the mediating role of employee skills, attidute and behaviour in construction industry - Ali, Mohamed Elfadeel (2019)
The current issue of HRM practices in the Libyan construction industry, they have lack of knowledge to handle human capital in the construction industry. Libyan industries as rely seriously on the skills, attitude and behavior of the foreign experts due to the lack of the local skilled force and it is challenging to Libya industries especially in the construction industry. Thus, this study examined the relationship between HRM practices and skills, attitude, and behavior, examined the relationship between HRM and organisational performance, examined the relationship between skills, attitude and behavior with organisational performance, investigated the mediating role of employee skills, employee attitude and employee behavior in relationship between HRM and organisational performance and developed the framework of the relationship between HRM and organisational performance. Data collected from employees working at the 632 Libyan construction companies by using the random sampling technique. There are 219 construction employees as the respondents this research in area Wadi al Shatii, Tripoli, Misrata, Al Zawiah, Sabha and Benghazi. A set of questionnaires was used for the data gathering. The data were analyzed using Structural Equation Modeling technique using AMOS 23 software. The findings showed that HRM was influenced employee skills, employee attitude and employee behavior and impact to organisational performance. The result also demonstrated that the employee skills, employee attitude and employee behavior are the mediator in the relationship between HRM and organisational performance. Meanwhile, the relationship between HRM and organisational performance is not supported. The contribution of this study proposed and validated a new framework in the Libyan construction companies it will facilitate the managers in creating and modifying their organisational policies and rules regarding human resource recruitment, selection, training and development to increase the productivity and competitiveness of the organisation.